The role and challenges met by parents in the implementation of modular distance learning in Mathematics / Breix Michael G. Agua and Jay A. Balasabas - Agua, Breix Michael G.; Balasabas, Jay A. (Research Management Institute (RMI), 2022)
COVID-19 has had a significant impact on the Philippine educational system. The country shifted from face-to-face classes to distance learning, including modular distance learning. Parents play a vital role in the success of said learning modality. The present study examined the parents level of understanding of the Mathematical contents, and their extent of parental roles and challenges encountered. It also determined relationships between the parental roles and profile variables versus the encountered level of challenges. Lastly, the study enumerates possible solutions to challenges met by parents. The study was participated by 118 parents. Frequencies and percentage distribution were used to describe the parents; profiles. Net agreement ratings were computed to measure the parents' understanding of the contents of Mathematics and the extent of the roles. The challenges met by parents were the indicators of the level of knowledge of the contents of Mathematics with negative net agreement ratings. It was unveiled that educational attainment and family monthly income are significantly related to the extent of challenges. Moreover, in implementing modular distance learning in Mathematics, parents as monitors, content advisers, and learning counselors were significantly related to the extent of challenges met by parents in implementing modular distance learning in Mathematics.